Cytotoxicity and genotoxicity caused by yttrium oxide nanoparticles in HEK293 cells - Selvaraj V (Dove Medical Press, 2014)
Vellaisamy Selvaraj,1 Sravanthi Bodapati,1 Elizabeth Murray,2 Kevin M Rice,1 Nicole Winston,1,3 Tolou Shokuhfar,4 Yu Zhao,4 Eric Blough1,3,5 1Center for Diagnostic Nanosystems, 2Department of Integrated Science and Technology, 3Department of Pharmaceutical Sciences and Research, School of Pharmacy, Marshall University, Huntington, WV, USA; 4Department of Mechanical Engineering and Engineering Mechanics, Michigan Technological University, Houghton, MI, USA; 5Department of Pharmacology, Physiology and Toxicology, School of Medicine, Marshall University, Huntington, WV, USA Background: The increased use of engineered nanoparticles (NPs) has caused new concerns about the potential exposure to biological systems and the potential risk that these materials may pose on human health. Here, we examined the effects of exposure to different concentrations (0–50 µg/mL) and incubation times (10 hours, 24 hours, or 48 hours) of yttrium oxide (Y2O3) NPs on human embryonic kidney (HEK293) cells. Changes in cellular morphology, cell viability, cell membrane integrity, reactive oxygen species levels, mitochondrial membrane potential, cell death (apoptosis and necrosis), and the DNA damage after NP exposure were compared to the effects seen following incubation with paraquat, a known toxicant. Results: The 24-hour inhibitory concentration 50 (IC50) of Y2O3 NPs (41±5 nm in size) in the HEK293 cells was found to be 108 µg/mL. Incubation with Y2O3 NPs (12.25–50 µg/mL) increased the ratio of Bax/Bcl-2, caspase-3 expression and promoted apoptotic- and necrotic-mediated cell death in both a concentration and a time-dependent manner. Decreases in cell survivability were associated with elevations in cellular reactive oxygen species levels, increased mitochondrial membrane permeability, and evidence of DNA damage, which were consistent with the possibility that mitochondria impairment may play an important role in the cytotoxic response. Conclusion: These data demonstrate that the Y2O3 NP exposure is associated with increased cellular apoptosis and necrosis in cultured HEK293 cells. Keywords: yttrium oxide nanoparticles, cytotoxicity, mitochondria damage, DNA damage, ROS production, apoptosis, necrosis